2005
DOI: 10.1080/00498250500153838
|View full text |Cite
|
Sign up to set email alerts
|

Growth and hepaticin vitrometabolism of ergotamine in mice divergently selected for response to endophyte toxicity

Abstract: This study investigated if genetic differences exhibited in endophyte-resistant and -susceptible mouse lines had persisted after 13 generations in which the integrity of lines was maintained yet selection ceased. Experimental groups were mouse lines fed an endophyte-free (E-) or -infected (E+) diet. The in vitro metabolism of the ergot alkaloid ergotamine in mouse liver microsomes was characterized by LC-MS/MS and compared between both lines before and after exposure to E+ feed. No difference in the average da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
6
18
0
Order By: Relevance
“…Erythromycin is a substrate of subfamily P450 3A, which is involved in the metabolism of ergot alkaloids, its inhibition leading to toxicity (Liaudet, 1999). Species and gender differences have been reported in in vitro metabolism of ergotamine, an alkaloid similar to EV, and it has been suggested that these differences could explain variations in sensitivity to fescue toxicosis (Duringer et al, 2005;Moubarak et al, 2006). Breed differences have also been cited to explain the differences in the prevalence of fescue toxicosis around the world.…”
Section: Drug Metabolizing Enzyme Activitiesmentioning
confidence: 99%
“…Erythromycin is a substrate of subfamily P450 3A, which is involved in the metabolism of ergot alkaloids, its inhibition leading to toxicity (Liaudet, 1999). Species and gender differences have been reported in in vitro metabolism of ergotamine, an alkaloid similar to EV, and it has been suggested that these differences could explain variations in sensitivity to fescue toxicosis (Duringer et al, 2005;Moubarak et al, 2006). Breed differences have also been cited to explain the differences in the prevalence of fescue toxicosis around the world.…”
Section: Drug Metabolizing Enzyme Activitiesmentioning
confidence: 99%
“…The kupffer cells of liver regulate the inflammatory processes and promote liver cancer by expressing TREM1. The TREM-1 is involved in liver carcinogenesis due to chronic inflammation, which slowly develops into tumors that gradually metastasizes [14]. The inhibition of the TREM-1 signaling pathway can possibly be a rational target for clinical situations to manage human HCC [15].…”
Section: Introductionmentioning
confidence: 99%
“…HepG2 cell line showed expression of p53 by Western blotting [17]. HGF has an oncogenic potential in the generation of HCC observed from the molecular details of HepG2 cell line [14]. However, meager reports are available for TREM1 protein, which plays a crucial role in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…After eight generations of relaxed selection, however, growth rate from weaning to 3 months of age of S and R males was similarly affected by the toxin-containing diet (Ross et al 2004). Subsequently, after 15 generations of relaxed selection, the effect of the toxin-containing diet on postweaning gain was non-significantly greater in R than in S individuals (Duringer et al 2005). Thus, line differences for some traits related to toxin resistance may have been attenuated prior to initiation of the current experiment, reducing the potential for interaction between resistance mechanisms and intensity of reproduction.…”
Section: Discussionmentioning
confidence: 91%
“…2004). Subsequently, after 15 generations of relaxed selection, the effect of the toxin‐containing diet on postweaning gain was non‐significantly greater in R than in S individuals (Duringer et al. 2005).…”
Section: Discussionmentioning
confidence: 99%